Meaning and context in the Thanksgiving Hymns : linguistic and rhetorical perspectives on a collection of prayers from Qumran - Hasselbalch, Trine (Atlanta : SBL Press, 2015)
"This book challenges the consensus that the Hodayot consist of leader hymns and community hymns respectively, and it breaks with the habit of interpreting each hymn as expressing basically either leadership issues or ordinary community member issues. Instead it argues that all of the compositions in 1QHodayota were perceived by their owners to express the sentiments of a worshipping community at large, and that the members of this community saw themselves as holding a mediating position in the agency of God. This way, the Hodayot express a theology according to which God acts in the world through the members of this particular community, and the collection of 1QHodayota seems to reflect an emergent socio-religious pattern which is different from that of the Book of Psalms. The book engages in an array of methods, most prominently from the field of sociolinguistics, in an attempt to find more sophisticated ways to approach the relationship between the Dead Sea scrolls, in this case the Hodayot, and their socio-historical contexts"--
Machine generated contents note: 1. Introduction -- 1.1. Composite Nature of 1 QHodayota -- 1.2. Social Implications of a Literary Bifurcation? -- 1.3. Fundamental Assumptions of This Study -- 1.4. Research Problem -- 1.5. Approaches -- 1.6. Compositions Analyzed in This Book -- 2. Special Methodological Issues -- 2.1. Systemic Functional Linguistics: A Brief Introduction -- 2.2. Three Textual Functions -- 2.3. Text and Context -- 2.4. Merits of SFL for This Project -- 2.5. Test Case: Analysis of 1 QHa X 22 -- 32 -- 3. Leadership and Credibility: 1QHa VI 19 -- 33 -- 3.1. Extent and Delimitation -- 3.2. Text, Transitivity, and Modality -- 3.3. Prayer Seen in a Performance Perspective -- 3.4. Excursus: Modality in Hebrew -- 4. Two Compositions Spoken by a Maskil: 1QHa XX 7 -- XXII 39 and 1QS IX 12 -- XI 22 -- 4.1. Introduction to 1QHa XX 7 -- XXII 39 -- 4.2. 1QSIX 12 -- XI 22 for Comparison -- 4.3. 1QHa XX 7 -- XXII 39 in the Light of 1QS IX 12 -- XI 22 -- 5. Merging of Traditions in a Classical Hybrid: 1QHa XII 6 -- XIII 6 -- 5.1. 1QHa XII 7 -- 30: Retold Drama -- 5.2. 1QHa XII 30 -- 34: Anthropological Section -- 5.3. 1QHa XII 34 -- XIII 6: Contemplation of God's Salvation -- 5.4. Speaker as a Unifying Factor -- 5.5. Knowledge as a Unifying Factor -- 5.6. Who Is Persuading Whom? -- 5.7. Mediator Perspectives in 1QHa XII 6 -- XIII 6 -- 5.8. Mingled Epistemologies and Rhetorical Meaning -- 6. Two Voices in Unison: The Self-Glorification Hymn and the Hymn of the Righteous -- 6.1. Identity of the Speaker -- 6.2. Approximations -- 6.3. Multifaceted Identity for the Community -- 7. Recapitulation and Recontextualization: Social and Mental Contexts for the Hodayot -- 7.1. Recapitulation -- 7.2. Multiple Roles in the Divine Agency -- 7.3. Mental Models and Context Models -- 7.4. More Recontextualization -- 8. Conclusions.
Includes bibliographical references (pages 275-293) and indexes.
Print version record.
Master record variable field(s) change: 050
Keywords: Thanksgiving Psalms; Dead Sea scrolls; Dead Sea scrolls; Thanksgiving Psalms; Hymns, Hebrew -- History and criticism; Qumran community; RELIGION -- Judaism -- General; Hymns, Hebrew; Qumran community; Electronic books; Criticism, interpretation, etc